Molecularly imprinted polymer for Mucin 4 (MUC4) biomarker - Piloto, A.M.L. (2024)
(Introduction) Molecularly imprinted polymers (MIPs) were synthesized around quantum dots (QDs) to detect the protein biomarker MUC4, which is associated with pancreatic cancer (Kauretal.,2022; Mehrotraetal.,2024). In this approach, MIPs serve as biorecognition elements and are conjugated with cadmium telluride QDs to form the sensing system. The fluorescence of these imprinted polymers is quenched as MUC4 concentrations increase, demonstrating a linear response within the range of 0.12 ng/mL to 16.9 ng/mL in human serum. This range is below the pancreatic cancer diagnostic cut-off values (1.2 to 1.3 ng/mL). The MIPs exhibit good stability and selectivity for MUC4 compared to non-imprinted controls. Additionally, theoretical studies provide valuable insights for the prediction of the functional structure of MIPs, enhancing its selectivity for the target, while reducing time and costs associated with laborious benchtop assays, which may provide an effective tool for tailoring MIPs to other biomarkers for clinical diagnosis.